Kerja Sama Indonesia-Korea Selatan dalam Pengelolaan Kebakaran Hutan di Ogan Komering Ilir: Dari Sekuritisasi ke Tata Kelola Adaptif - Rivai, Ferdiansyah; Wijaya, Bagaskara Sagita; Syuryansyah, Syuryansyah; Amalia, Ridha (Jurusan Ilmu Politik Universitas Bangka Belitung, 2026)
Forest and land fires in Ogan Komering Ilir (OKI), South Sumatra, continue to pose a persistent environmental challenge. This study examines Indonesia–South Korea cooperation through the Korea–Indonesia Forest Cooperation Center (KIFC), which was established in response to the securitisation of forest fires and has evolved into a model of adaptive governance. By examining KIFC, this article demonstrates that securitization enables international cooperation and technical control, yet simultaneously constrains deeper adaptive governance needed to address local fire drivers. By employing a qualitative case study approach, this research examines KIFC's initiatives from 2015 to 2024, utilizing a combination of document analysis, policy review, and field observations. The findings show that while KIFC introduced advanced monitoring systems and early warning technologies, local economic dependence on land-clearing and fragmented governance remain significant barriers. This study argues that KIFC has succeeded technically but faces challenges in addressing deeper structural issues. The cooperation's success hinges on the alignment of external technical solutions with local socio-economic realities and the fostering of community-based resilience. This study contributes to understanding how international cooperation can bridge the gap between securitization and adaptive governance, offering lessons for future sustainable environmental governance in Indonesia and beyond.